Biomass-derived carbonaceous positive electrodes for sustainable lithium-ion storage. Issue 6 (26th January 2016) - Liu, Tianyuan; Kavian, Reza; Chen, Zhongming; Cruz, Samuel S.; Noda, Suguru; Lee, Seung Woo
Abstract : We demonstrate that carbon sphere products obtained from glucose by a hydrothermal carbonization process have redox-active properties with lithium ions. Abstract : Biomass derived carbon materials have been widely used as electrode materials; however, in most cases, only electrical double layer capacitance (EDLC) is utilized and therefore, only low energy density can be achieved. Herein, we report on redox-active carbon spheres that can be simply synthesized from earth-abundant glucose via a hydrothermal process. These carbon spheres exhibit a specific capacity of ∼210 mA h gCS −1, with high redox potentials in the voltage range of 2.2–3.7 V vs . Li, when used as positive electrode in lithium cells. Free-standing, flexible composite films consisting of the carbon spheres and few-walled carbon nanotubes deliver high specific capacities up to ∼155 mA h gelectrode −1 with no obvious capacity fading up to 10 000 cycles, proposing to be promising positive electrodes for lithium-ion batteries or capacitors. Furthermore, considering that the carbon spheres were obtained in an aqueous glucose solution and no toxic or hazardous reagents were used, this process opens up a green and sustainable method for designing high performance, environmentally-friendly energy storage devices.